Підвищення ефективності використання твердопаливних топок - Стручаєв, Микола Іванович; Стручаев, Николай Иванович; Struchaiev, Mykola; Постол, Юлія Олександрівна; Постол, Юлия Александровна; Postol, Yuliia; Борохов, Іван Валерійович; Борохов, Иван Валерьевич; Borokhov, Ivan (ТДАТУ, 2019)
UK: В роботі розглянуто вплив режимів використання енергії палива на ефективність роботи системи опалення для одного із варіантів роботи твердопаливних топок шляхом зниження втрат палива, зменшення теплового напруження топкового простору за рахунок регулювання процесу горіння. Розглянуто алгоритм розрахунку та аналізу таких параметрів роботи топки, як: теплове напруження топкового простору, питома годинна витрата палива, кількість теплоти, яку топка виділяє за годину та маса палива, яку спалюють в топці за одну топку з метою підвищення енергоефективності. Запропоновано емпіричні формули розрахунку енергетичних параметрів топок малої потужності. RU: В работе рассмотрено влияние режимов использования энергии топлива на эффективность работы системы отопления для одного из вариантов работы твердотопливных топок путем снижения потерь топлива, уменьшения теплового напряжения топочного пространства за счет регулирования процесса горения. Рассмотрены алгоритм расчета и анализа таких параметров работы топки, как: тепловое напряжение топочного пространства, удельный часовой расход топлива, количество теплоты, которое топка выделяет в час и масса топлива, которую сжигают в топке за одну топку с целью повышения энергоэффективности. Предложены эмпирические формулы расчета энергетических параметров топок малой мощности. EN: The paper discusses the influence of fuel energy use on the efficiency of the heating system for one of the options for operating solid fuel furnaces by reducing fuel losses and reducing the heat stress of the combustion space by controlling the combustion process. The algorithm for calculating and analyzing such parameters of the firebox as the heat stress of the combustion space, the specific hourly fuel consumption, the amount of heat that the firebox emits per hour and the mass of fuel that is burned in the firebox for one firebox in order to improve energy efficiency are considered. Suggestions empirical formulas for calculating the energy parameters of low-power furnaces. The purpose of this article is to increase the energy efficiency of heating systems by optimizing the combustion regimes for solid fuel furnaces. The amount of heat that the furnace emits per hour is significantly reduced, but the temperature in the room heated becomes more comfortable and uniform. So for example, provided when burning the entire amount of fuel for one firebox with a duration of 1:00, the room temperature increases sharply to 27°C and then gradually decreases to +14°C. When burning the entire amount of fuel for one 3 furnaces with a duration of 1:00, the temperature in the room is kept constant at + 18°C. The algorithm for calculating and analyzing such parameters of the firebox as the heat stress of the combustion space, the specific hourly fuel consumption, the amount of heat that the firebox emits per hour and the mass of fuel that is burned in the firebox for one firebox are proposed. Empirical formulas for determining the change in the basic energy parameters of a solid-fuel furnace operation depending on the combustion regimes are obtained. The proposed method of calculation and analysis can be used for the selection of operating modes of solid-fuel furnaces with the aim of increasing energy efficiency.
Повышение эффективности использования твердотопливных топок
Increas the energy efficiency of solid fuel boilers
Keywords: теплове напруження топкового простору; питома годинна витрата палива; кількість теплоти; маса палива; підвищення енергоефективності